Effect of fluoride-treated enamel on indirect cytotoxicity of a16% carbamide peroxide bleaching gel to pulp cells - Soares, Diana Gabriela [UNESP]; Ribeiro, Ana Paula Dias; Lima, Adriano Fonseca; Sacono, Nancy Tomoko; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this study was to evaluate the possibility of fluoride solutions applied to enamel to protect pulp cells against the trans-enamel and transdentinal cytotoxicity of a 16% carbamide peroxide (CP) bleaching gel. The CP gel was applied to enamel/ dentin discs adapted to artificial pulp chambers (8 h/day) during 1, 7 or 14 days, followed by fluoride (0.05% or 0.2%) application for 1 min. The extracts (culture medium in contact with dentin) were applied to MDPC-23 cells for 1 h, and cell metabolism (MTT assay), alkaline phosphatase (ALP) activity and cell membrane damage (flow cytometry) were analyzed. Knoop microhardness of enamel was also evaluated. Data were analyzed statistically by ANOVA and Kruskal-Wallis tests (a=0.05). For the MTT assay and ALP activity, significant reductions between the control and the bleached groups were observed (p<0.05). No statistically significant difference occurred among bleached groups (p>0.05), regardless of fluoride application or treatment days. Flow cytometry analysis demonstrated 30% of cell membrane damage in all bleached groups. After 14 days of treatment, the fluoride-treated enamel presented significantly higher microhardness values than the bleached-only group (p<0.05). It was concluded that, regardless of the increase in enamel hardness due to the application of fluoride solutions, the treated enamel surface did not prevent the toxic effects caused by the 16% CP gel to odontoblast-like cells.
Keywords: Carbamide peroxide; Cytotoxicity; Odontoblast; Tooth bleaching